Exploring managerial values in the changing Turkish business context - Cakmakci, Ufuk M.; Karabati, Serdar (Emerald Group Publishing Ltd, 2008)
Purpose - The aim of this paper is to explore differences in managerial values in Turkey by relating them to the changing business context. Design/methodology/approach - The research delineates individual value differences between upper-level managers and a group of MBA students who were approached through a questionnaire and in- depth interviews. Findings - The basic findings support the view that workplace socialisation may affect individual values and practices. Research limitations/implications - The limitation of this paper is its exploratory nature based on the small sample size of research. Practical implications - In the context of internationalization and rising competition within the economic space, change should be high on the agenda of the Turkish private sector in adapting to the shifts in business environment. This should incorporate professional training as well as strategic HR projects aiming to transform the existing structures biased toward paternalism. Originality/value - The paper contributes to the existing management literature by identifying critical value dilemmas facing Turkish businesses in today's turbulent and internationalized business environment.
Keywords: Turkey; Management Culture; Innovation; Value Analysis; Business Environment; Individualism; Collectivism; Organization; Bureaucracy; Cultures; Turkey